2015
DOI: 10.17722/ijme.v5i1.194
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Safety Climate on Safety Performance in a Gold Mining Company in Ghana

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Situational factors are related to safety climate and safety leadership 10,11 The results explained before were in line with the statements of Vinodkumar and Bhasi who found that safety management practices had influence on safety performance 8 . Apart from being in line with the theory put forward by Vinodkumar & Bhasi, the results of this study were also in line with research by Froko et al which found that there was a positive correlation between safety climate and safety performance that could predict compliance and safety participation 12 . Safety management practices had direct significant influence towards safety performance through its six indicators consisting of management commitment, safety training, worker involvement in solving safety problems, safety communication and feedback, safety rules and procedures, and safety promotion policies.…”
Section: Discussionsupporting
confidence: 91%
“…Situational factors are related to safety climate and safety leadership 10,11 The results explained before were in line with the statements of Vinodkumar and Bhasi who found that safety management practices had influence on safety performance 8 . Apart from being in line with the theory put forward by Vinodkumar & Bhasi, the results of this study were also in line with research by Froko et al which found that there was a positive correlation between safety climate and safety performance that could predict compliance and safety participation 12 . Safety management practices had direct significant influence towards safety performance through its six indicators consisting of management commitment, safety training, worker involvement in solving safety problems, safety communication and feedback, safety rules and procedures, and safety promotion policies.…”
Section: Discussionsupporting
confidence: 91%
“…According to the correlation analysis results regarding the relationship between dimensions of safety climate and safety participation, there is a significant relationship between safety participation and both dimensions of safety climate (p<0.01). Froko & Umar (2015) found a significant relationship between the control practices dimension of safety climate and safety participation in their studies with mine workers. In addition, in their study with workers from the manufacturing and mining industries, Neal & Griffin (2000) have concluded that safety climate directly affects safety performance (safety compliance and safety participation).…”
Section: Discussionmentioning
confidence: 92%
“…Results of these studies suggest that there is a positive relationship between safety climate and safety behaviours (Neal et al, 2000;Neal & Griffin, 2000;Garcia et al, 2004;Cooper & Philips, 2004;Wu et al, 2008;Zhu et al, 2010;Lu & Yang, 2011;Kundu et al, 2015;Froko & Dursun, S. & B. Şengül (2023), "The Relationship Between Safety Climate and Safety Performance Indicators: A Field Study", Sosyoekonomi, 31(55), 37-48. Umar, 2015;Jusoh & Panatik, 2016;Al-Zubaidi & İmamoğlu, 2017;Hosny et al, 2017;Boshoff et al, 2017;Lyu et al, 2018;Lee et al, 2019;Changquan et al, 2020;Elmoujaddidi & Bachir, 2020;Saedi & Majid, 2020;Yücebilgiç, 2007;Sadullah & Kanten, 2009;Yorulmaz et al, 2016;Ören & Er, 2016). In addition, some studies have reported a significant relationship between safety climate and exposure to occupational accidents or near-miss incidents (Williamson et al, 1997;Evans et al, 2005;Hahn & Murphy, 2008;Vinodkumar & Bhasi, 2008;Karadal & Merdan, 2017).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…However, there are only a few studies in the context of Ghana. The majority were conducted in other fields including drivers of haulage companies (Amponsah-Tawiah and Mensah, 2016), fuel station attendants (Bakidamteh, 2018) and mine workers (Froko et al. , 2015), completely neglecting the construction industry.…”
Section: Introductionmentioning
confidence: 99%